Eyewitness Memory in Face-to-Face and Immersive Avatar-to-Avatar Contexts - Taylor, Donna A.; Dando, Coral J. (Frontiers in Psychology, 2018)
Technological advances offer possibilities for innovation in the way eyewitness testimony is elicited. Typically, this occurs face-to-face. We investigated whether a virtual environment, where interviewer and eyewitness communicate as avatars, might confer advantages by attenuating the social and situational demands of a face-to-face interview, releasing more cognitive resources for invoking episodic retrieval mode. In conditions of intentional encoding, eyewitnesses were interviewed 48 hours later, either face-to-face or in a virtual environment (N= 38). Participants in the virtual environment significantly outperformed those interviewed face-to-face on all episodic performance measures – improved correct reporting reduced errors, and increased accuracy. Participants reported finding it easier to admit not remembering event information to the avatar, and finding the avatar easier to talk to. These novel findings, and our pattern of retrieval results indicates the potential of avatar-to-avatar communication in virtual environments, and provide impetus for further research investigating eyewitness cognition in contemporary retrieval contexts.